Tire strain piezoelectric energy harvesters: a systematic review - Ibrahim Ali Hameed Al-Najati; Keng Wai Chan; Swee-Yong Pung (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Intelligent tires are regular tires with additional sensors attached to measure different parameters, such as pressure, temperature, and tire dynamic condition. Sensors mounted inside tires are usually powered by batteries. An alternative power source for these sensors is piezoelectric energy, which uses piezoelectric patches that can be mounted close to the sensors inside vehicle tires. Piezoelectric energy is a battery-less energy source with a long lifespan and environmentally friendly characteristics. This paper presents a comprehensive review of piezoelectric energy harvesters that harvest vehicle tire strain and convert it to electrical energy to power inner tire sensors. The aim of this review was to characterize the possible available tire piezoelectric strain energy harvesters and their advantages and challenges for each type, shape, and material used by researchers so far. The related articles were categorized according to the installation method of the harvester inside the vehicle tire. The four categories are inner tire treadwall, tire bead–rim interface, tire inner sidewall, and tire bead. The maximum power generated was 2300 mW from a treadwall tire strain piezoelectric harvester. Ten challenges were mentioned and classified into three main groups: host environment, installation method, and scavenging system.